Working from home and stress among lecturers: a review / Zainuddin Mohd Piah ... [et l.] - Mohd Piah, Zainuddin; Anuar, Azyyati; Selvaraj, Bawani (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
The year 2020 was a year of change to the working environment when the COVID-19 pandemic sent shockwaves not only in Malaysia but also across the globe. This pandemic had seriously affected on higher education as universities shut their premises and countries closed their borders due to lockdown measures (Schleicher, 2020). Interestingly, this pandemic created new environmental norms in the education sector and there has also been hasty and enormous changes in the workplace, from the office to working from home (Schifano et al., 2021; Palumbo et al., 2020). According to Kramer and Kramer (2020), work from home (WFH) is defined as the method involved with working outside of physical space, supported by technology that decreases commuting time and further develops proficiency. Similarly, WFH is otherwise called as remote work (RW), telecommuting, teleworking, schoolwork, workspace, outwork, mobile work, and the adaptable work environment, is a work plan, in which representative do not transport to their work environment in the organization (Bellmann & Hübler, 2020).